Miocene snakes from northeastern Kazakhstan: new data on the evolution of snake assemblages in Siberia. (26th November 2019) - Ivanov, Martin; Vasilyan, Davit; Böhme, Madelaine; Zazhigin, Vladimir S.
Abstract: The Neogene snake fauna from the central and eastern regions of Eurasia is still largely unknown. This paper reports on a unique snake fauna from the late middle Miocene of the Baikadam and Malyi Kalkaman 1 and 2 localities, northeastern Kazakhstan, which represents the best-documented Miocene snake assemblage in Central Asia. Previous studies admitted that snake fauna could be homogeneous over a large part of Eurasia during the Miocene, with the late middle to early late Miocene assemblages similar to snake assemblages that inhabited Europe in the late early and early middle Miocene. This assumption is partially supported by the presence of Texasophis bohemiacus and Coluber cf. hungaricus, as well as vipers of the ' V. aspis ' complex. However, the presence of taxa which are (1) probably not related to European representatives ('Colubrinae' A and B), (2) probably never occurred in Central and Western Europe and (3) are closely related to species recently inhabiting southern Siberia ( Elaphe aff. dione, Gloydius sp.) indicates that faunal dissimilarity was relatively high within Eurasia during the late middle Miocene. This assumption is in accordance with studies of small mammal assemblages which show a decreasing homogenity in the Eurasia in the course of the middle Miocene.